The Influence of Audit Quality, Audit Tenure, and Nature of Industry on Financial Statement Fraud at Main Board Infrastructure Companies Registered in BEI in 2019-2021 - Noverta Wiguna Revaldi; Richard Friendly Simbolon (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2023)
Financial statement fraud is an omission in disclosure as a goal in deceiving users of financial statements, according to PPATK that infrastructure is the sector most prone to corruption and money laundering. This study aims to confirm the effect of audit quality, tenure auditors, accounting firm tenure, and nature of industry on fraudulent financial statements of infrastructure companies during the three years Ã‚Â of research from 2019-2021, fifty sample infratructure companies were obtained with the total sample data studied as many as one hundred and twelve samples using purposive sampling method in the collection method. This study uses descriptive analysis methods with multiple linear regression. The results show that simultaneously audit quality, audit tenure, KAP tenureee and nature of industry has a significant effect on financial statement fraud but partially audit quality, KAP tenure, and nature of industry has a significant effect on financial statement fraud while audit tenure has no effect on financial statement fraud.